Gene set analysis of lung samples provides insight into pathogenesis of progressive, fibrotic pulmonary sarcoidosis. - Lockstone, H; Sanderson, S; Kulakova, N; Baban, D; Leonard, A; Kok, W; McGowan, S; Mcmichael, A; Ho, L (2010)
RATIONALE: Approximately 60 to 70% of patients with pulmonary sarcoidosis have disease that resolves spontaneously; the rest follow a chronic course with varying levels of fibrosis. It is unclear why some patients progress and if treatment affects outcome. OBJECTIVES: To determine differential gene expression profile in lungs of patients with self-limiting sarcoidosis compared to those with progressive-fibrotic disease, and to analyze the biological relevance of these differentially expressed genes. METHODS: We examined microarray expression of 26,626 genes in transbronchial biopsies of granulomatous areas in lungs of patients with active but self-limiting (n = 8) versus those with active, progressive (+/- fibrotic) pulmonary disease (n = 7). MEASUREMENTS AND MAIN RESULTS: Three hundred thirty-four genes were differentially expressed between the two groups (P < 0.01, Bayesian moderated t test). Gene Set Enrichment Analysis showed over-representation of gene-sets (defined by Gene Ontology) related to host immune activation, proliferation, and defense, among genes up-regulated in the progressive-fibrotic group (FDR q < 0.0001 for the top 43 gene sets), and a marked enrichment of, and similarity in gene expression profiles between, progressive-fibrotic sarcoidosis and hypersensitivity pneumonitis (HP), (q < 0.001), but not idiopathic pulmonary fibrosis (IPF). CONCLUSIONS: The findings suggest that patients with progressive/fibrotic pulmonary sarcoidosis have intense immune activity related to host defense in their lungs, with processes more similar to HP than IPF. The study also demonstrates that transbronchial lung biopsy samples can provide good-quality RNA for gene expression profiling, supporting its potential use as a prognostic classifier for pulmonary sarcoidosis.